"Bringing greater research fluency into our educational vision": A qualitative research study on improving Traditional Chinese Medicine research education. - Heidi Most; Lisa Conboy; Rosaleen Ostrick; Belinda J Anderson (PLoS ONE)
The main objective of this qualitative analysis is to increase the quality of Traditional Chinese Medicine (TCM) research education. Subject matter experts and stakeholders were sent a list of possible topics to include in a research course and were asked to comment on it, add or subtract topics, and suggest appropriate research papers to use, lessons learned in their topic areas and possible stand-alone topics for inclusion in other courses. Their feedback was used to revise the topic list, create a list of foundational research papers to include in a research course and devise a list of stand-alone topics that could be included in the general TCM research curriculum. The result is a TCM research course curriculum that will improve the teaching of evidence-based medicine (EBM) practices to TCM students. This will help TCM faculty and program directors improve existing courses, develop new courses and strengthen EBM education.